The percetions specialized in laring sport initiation of rítmica gymnastic: games for your training (Original) (Revista científica Olimpia, 2019)
This article refers to a topic of great importance in the world of Physical Activity and Sport, such as the application of Psychology in sports initiation (4-5 years), specifically in Rhythmic Gymnastics, is the result of actions developed as part of the Community Project of Rhythmic Gymnastics "Nene Traviesa" of the UCCFD "Manuel Fajardo de La Habana", conceived as an alternative to new forms of training to promote psychological preparation, where gymnasts learn and play at the same time. It intends to substantiate the role that specialized perceptions play as one of the psychological demands that affect sports performance in Rhythmic Gymnastics and, from there, propose games according to the characteristics of girls of 5 and 6 years old, selected sample for the present investigation.
Keywords: rhythmic gymnastics; games; specialized perceptions